2007
DOI: 10.1128/jcm.00533-07
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity and Microsphere Array-Based Genotyping of Human Pathogenic Fusaria, Including Isolates from the Multistate Contact Lens-Associated U.S. Keratitis Outbreaks of 2005 and 2006

Abstract: To characterize the full spectrum of the causal agents involved and their potential sources, partial DNA sequences from three loci (RPB2, EF-1␣, and nuclear ribosomal rRNA) totaling 3.48 kb were obtained from 91 corneal and 100 isolates from the patient's environment (e.g., contact lens and lens cases). We also sequenced a 1.8-kb region encoding the RNA polymerase II second largest subunit (RPB2) from 126 additional pathogenic isolates to better understand how the keratitis outbreak isolates fit within the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
209
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(220 citation statements)
references
References 42 publications
7
209
1
3
Order By: Relevance
“…Primers for molecular identification and phylogenetic analysis Primers ITS1 (TCCGTAGGTGAACCTGCGG) and ITS4 (TCCTCCGCTTATTGATATGC) were used to amplify the ITS fragment (approximately 600 bp), primers EF1 (ATGGGTAAGGARGACAAGAC) and EF2 (GGARGTACCAGTSATCATGTT) were used to amplify a nearly 720 bp fragment of the coding gene for EF-1α, primers RPB2-5F (GAYGAYMGWGATCAYTTYGG) and RPB2-7R (CCCATWGCYTGCTTMCCCAT) were used to amplify a nearly 1200 bp fragment of the coding gene for RPB2 O'Donnell et al 2007, O'Donnell et al 2008Short et al 2011;Zhang et al 2006). DNA extraction and polymerase chain reaction DNA was extracted using a manual purification procedure as described (Papizadeh et al 2017a,;Saba et al 2016).…”
Section: Growth Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers for molecular identification and phylogenetic analysis Primers ITS1 (TCCGTAGGTGAACCTGCGG) and ITS4 (TCCTCCGCTTATTGATATGC) were used to amplify the ITS fragment (approximately 600 bp), primers EF1 (ATGGGTAAGGARGACAAGAC) and EF2 (GGARGTACCAGTSATCATGTT) were used to amplify a nearly 720 bp fragment of the coding gene for EF-1α, primers RPB2-5F (GAYGAYMGWGATCAYTTYGG) and RPB2-7R (CCCATWGCYTGCTTMCCCAT) were used to amplify a nearly 1200 bp fragment of the coding gene for RPB2 O'Donnell et al 2007, O'Donnell et al 2008Short et al 2011;Zhang et al 2006). DNA extraction and polymerase chain reaction DNA was extracted using a manual purification procedure as described (Papizadeh et al 2017a,;Saba et al 2016).…”
Section: Growth Ratesmentioning
confidence: 99%
“…For amplification of the selected fragment of the RPB2 gene the PCR conditions included: (1) hot start with 95°C for 5 min; (2) 30 cycles of 1 min at 95°C, 2 min at 55°C (or 50°C), an increase of 1°C/5 s to 72°C, and 2 min at 72°C; and (3) a 10-min incubation at 72°C, respectively. The PCR products were sequenced by Genfanavaran Biotech Corporation (O'Donnell et al 2007). The DNA sequences determined for this study were submitted to GenBank, and the accession numbers for strain CBS 115.40 = IBRC-M 30232 are: KX503270 (RPB2), KX503269 (EF-1α), KX503267 (ITS).…”
Section: Growth Ratesmentioning
confidence: 99%
“…Molecular phylogenetic studies of medically important fusaria have revealed that the more commonly reported pathogens (i.e., F. solani, F. oxysporum, F. moniliforme, F. incarnatum, F. chlamydosporum, and F. dimerum) actually comprise species complexes that collectively contain at least 70 species (15,(21)(22)(23)(24)(25)(26). Since the majority of fusarial isolates cannot be identified to species level by traditional morphological methods only (errors in identification, Ϸ33 to 50%), which greatly underestimate species diversity (19,22,24), DNA sequence-based molecular tools are increasingly used to enable accurate species determination (4,27).…”
mentioning
confidence: 99%
“…Recently, at least 300 phylogenetically distinct species were estimated (O'Donnell et al, 2015). O'Donnell et al (2004O'Donnell et al ( , 2007 and Zhang et al (2006) reported that fusaria pathogenic to humans and other animals belong to either the FSSC or FOSC clade. In light of the conclusion by Dupont et al (2007) regarding the Lascaux Cave, we suggested that most TT and KT fusaria in the FSSC clade 3 were also deeply involved in the deterioration of the murals .…”
Section: -1 Fusarium Solani Species Complex (Fssc) Cladementioning
confidence: 99%